A comparison between the efficiency of the Xpert MTB/RIF assay and nested PCR in identifying Mycobacterium tuberculosis during routine clinical practice - Kim, Cheol-Hong; Woo, Heungjeong; Hyun, In Gyu; Kim, Changhwan; Choi, Jeong-Hee; Jang, Seung-Hun; Park, Sang Myeon; Kim, Dong-Gyu; Lee, Myung Goo; Jung, Ki-Suck; Hyun, Jeongwon; Kim, Hyun Soo (Journal of Thoracic Disease, 2014)
Objectives: Polymerase chain reaction (PCR) for the detection of Mycobacterium tuberculosis (MTB) is more sensitive, specific, and rapid than the conventional methods of acid-fast bacilli (AFB) smear and culture. The aim of this study was to determine if the Xpert MTB/rifampicin (RIF) assay had additional advantages over nested PCR for the detection of MTB in a geographical area with intermediate tuberculosis (TB) incidence. Methods: Between February and December 2013, the Xpert MTB/RIF assay and MTB nested PCR, as well as AFB smear and culture, were simultaneously performed on 198 clinical samples (160 pulmonary and 38 non-pulmonary specimens) collected from 171 patients hospitalized at Hallym University Medical Center for possible TB. The accuracy of the diagnosis of MTB culture-positive TB and the turnaround time of reporting laboratory results were calculated and compared. Rifampin resistance by the Xpert MTB/RIF assay was reviewed with that of conventional drug susceptibility testing (DST). Results: The sensitivity, specificity, and positive and negative predictive values of the Xpert MTB/RIF assay and MTB nested PCR for diagnosis of MTB culture-positive pulmonary TB were 86.1% vs. 69.4% (P=0.1563), 97.8% vs. 94.1% (P=0.2173), 91.2% vs. 75.8% (P=0.1695), and 96.4% vs. 92.0% (P=0.2032), respectively. The median turnaround times of the Xpert MTB/RIF assay and MTB nested PCR were 0 [0-4] days and 4 [1-11] days, respectively (P